A mixed-method approach to generate and deliver rapid-cycle evaluation feedback: lessons learned from a multicenter implementation trial in pediatric surgery - Salva N. Balbale; Willemijn L. A. Schäfer; Teaniese L. Davis; Sarah C. Blake; Sharron Close; Gwyneth A. Sullivan; Audra J. Reiter; Andrew J. Hu; Charesa J. Smith; Maxwell J. Wilberding; Julie K. Johnson; Jane L. Holl; et al. (Implementation Science Communications, 2023)
Abstract Background Rapid-cycle feedback loops provide timely information and actionable feedback to healthcare organizations to accelerate implementation of interventions. We aimed to (1) describe a mixed-method approach for generating and delivering rapid-cycle feedback and (2) explore key lessons learned while implementing an enhanced recovery protocol (ERP) across 18 pediatric surgery centers. Methods All centers are members of the Pediatric Surgery Research Collaborative (PedSRC, www.pedsrc.org ), participating in the ENhanced Recovery In CHildren Undergoing Surgery (ENRICH-US) trial. To assess implementation efforts, we conducted a mixed-method sequential explanatory study, administering surveys and follow-up interviews with each center’s implementation team 6 and 12 months following implementation. Along with detailed notetaking and iterative discussion within our team, we used these data to generate and deliver a center-specific implementation report card to each center. Report cards used a traffic light approach to quickly visualize implementation status (green = excellent; yellow = needs improvement; red = needs significant improvement) and summarized strengths and opportunities at each timepoint. Results We identified several benefits, challenges, and practical considerations for assessing implementation and using rapid-cycle feedback among pediatric surgery centers. Regarding potential benefits, this approach enabled us to quickly understand variation in implementation and corresponding needs across centers. It allowed us to efficiently provide actionable feedback to centers about implementation. Engaging consistently with center-specific implementation teams also helped facilitate partnerships between centers and the research team. Regarding potential challenges, research teams must still allocate substantial resources to provide feedback rapidly. Additionally, discussions and consensus are needed across team members about the content of center-specific feedback. Practical considerations include carefully balancing timeliness and comprehensiveness when delivering rapid-cycle feedback. In pediatric surgery, moreover, it is essential to actively engage all key stakeholders (including physicians, nurses, patients, caregivers, etc.) and adopt an iterative, reflexive approach in providing feedback. Conclusion From a methodological perspective, we identified three key lessons: (1) using a rapid, mixed method evaluation approach is feasible in pediatric surgery and (2) can be beneficial, particularly in quickly understanding variation in implementation across centers; however, (3) there is a need to address several methodological challenges and considerations, particularly in balancing the timeliness and comprehensiveness of feedback. Trial registration NIH National Library of Medicine Clinical Trials. ClinicalTrials.gov Identifier: NCT04060303. Registered August 7, 2019, https://clinicaltrials.gov/ct2/show/NCT04060303